Case of Land Ownership Encroachment Reviewed from Agrarian Law Aspects: A Case Study of Verdict No: 255 K/TUN/2021 - Mirza Megananda; Akhmad Safik (PT Mattawang Mediatama Solution, 2024)
This study aims to analyze the cases of land expropriation of ownership rights from the perspective of agrarian law. Land expropriation is an increasingly frequent phenomenon, causing complex agrarian conflicts that require appropriate legal handling. The focus of this study is on the aspects of agrarian law related to cases of land expropriation, including land rights, agrarian regulations, and agrarian dispute resolution. The research methods used are normative juridical and empirical methods. The normative juridical approach is carried out by reviewing various laws, regulations, and policies related to agrarian law as well as literature studies to understand the legal framework governing land ownership. Meanwhile, the empirical juridical approach is conducted by analyzing data on land expropriation cases that have occurred, including the dispute resolution processes that have been carried out. The results of this study show that cases of land expropriation of ownership rights involve violations of the original owners' land rights. Factors such as lack of oversight, weak law enforcement, and unclear agrarian regulations contribute to the increase in land expropriation cases. From the perspective of agrarian law, protection of land rights needs to be strengthened through regulatory improvements and enhanced law enforcement. This study also highlights the importance of effective and fair agrarian dispute resolution. The dispute resolution process needs to involve active participation from all parties involved, including local communities and local governments. The implementation of alternative dispute resolutions, such as mediation and arbitration, can also be a quicker and more efficient solution.